Nanocrystalline Cellulose Isolation from Pulverized Kenaf Core using Hydrothermal Treatment with Low Concentration of Oxalic Acid - Akma Mohd Zuki, Syaidatul; Shaifudin bin Azman, Muhammad; Abd Rahman, Norazah; Fitrah Abu Bakar, Noor (International Journal of Engineering and Technology, 2018)
Isolation of nanocrystalline celluloses (NCC) from pulverized kenaf core (PKC) particles using hydrothermal treatment with low concentration of oxalic acid hydrolysis was investigated in this study. Prior to hydrolysis treatment, PKC particles were pretreated using alkali (NaOH) and bleaching treatments to eliminate lignin and hemicellulose. Zeta potential and particles size analysis showed that the zeta potential value and the average size of NCC obtained is -31.6 mV and 182.55 nm respectively. The median diameter, d50 for the NCC suspension is 316.72 nm. A rough surface of flake shape agglomerated NCC particles was shown in SEM image. Fourier transform infrared (FTIR) spectroscopy showed the removal of lignin and hemicellulose after alkali treatment and bleaching process since there is no peak at wavelength number of 1740 and 1590 cm-1. X-ray diffraction (XRD) analysis revealed that the crystallinity increased from 59.72% to 64.29%.